Un(intended) Language Planning in a Globalising World: Multiple Levels of Players at Work - Chua Siew Kheng, Catherine (De Gruyter, 2018)
This first book provides a comprehensive overview of the different levels of players who have been involved in both intended and unintended language planning and policy, and shows how they have impacted multilingual language use. Specifically, it looks at the roles of different ´glo-national` (global national) players in directing the choices of language use in various parts of the world. Drawing on topics from numerous countries i.e., Basque country, Brazil, China, Europe, France, Germany, Japan, Malaysia, North Korea, Philippines, Russia, Singapore, South Africa, Turkey, Vietnam, United Arab Emirates and the United States of America, this book showcases the complexity of language planning. The book not only provides examples to illustrate how globalisation has led to an increase in demand in learning English in many countries, it brings in other examples to demonstrate how globalisation has also promoted language diversity in other countries as well. Using the four stages of language planning framework - Supra Macro, Macro, Micro and Infra Micro levels of language planning, the book discusses the tension that surrounds the global, national and local demands on language choice, and presents the possible outcomes of the various intended and unintended policies, and strategies adopted by the different players found in these four stages of planning. The aim of the book is to highlight the importance of aligning the supra and macro levels of planning with the micro and infra macro levels of planning in any language planning in order to obtain positive outcomes.